(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2021)
The XII Central American Congress of Anthropology based at UNAN-Managua, has invited to live an interdisciplinary meeting, being Anthropology the study of human beings in all their manifestations, it is very important that they promote this space so that we meet and share the sociocultural realities that occur in our Mesoamerican region, with our peoples and natural resources. The essay entitled: Impacts of the neoliberal, patriarchal system on the territorial bodies of indigenous women in Honduras; Garífuna, Maya Chorti, Lenca, Pech, Tolupán and Misquito, contains the experiences lived in Honduras and systematized by the National Coordinator of Indigenous Women of Honduras. CONAMINH and the Black Fraternal Organization of Honduras. OFRANEH, both member organizations of the Jubileo South / Americas Network. These experiences show the serious consequences that the neoliberal system has caused the Honduran people, but which fall mainly on the bodies - territories of the women of ancestral native peoples and on Mother Earth.